2011
DOI: 10.1007/dcr.0b013e3181fb7b82
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function After Treatment for Rectal Cancer: A Review

Abstract: Sexual function is one element of QOL that may be significantly altered following treatment for rectal cancer, but the incidence and contributing risk factors are generally poorly understood. Nevertheless, the impact of rectal cancer therapy on sexual function should be conveyed to patients preoperatively. In addition to helping patients evolve realistic expectations, it will help clinicians identify those for whom interventions may be appropriate. In the past 10 years, there has been an increase in the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 47 publications
(54 reference statements)
5
102
1
7
Order By: Relevance
“…Although forty reviews met the inclusion criteria with respect to quality assessment, twenty-nine studies were eliminated because they were investigating the primary crc risk in general populations , and another three systematic reviews were eliminated because the original studies included in those reviews were of poor quality due to numerous methodologic flaws and inconclusive findings [54][55][56] . Thus, only the remaining eight reviews (seven systematic reviews and one meta-analysis) were included in our synthesis [57][58][59][60][61][62][63][64] . Figure 1 presents details of the search and inclusion and exclusion process.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although forty reviews met the inclusion criteria with respect to quality assessment, twenty-nine studies were eliminated because they were investigating the primary crc risk in general populations , and another three systematic reviews were eliminated because the original studies included in those reviews were of poor quality due to numerous methodologic flaws and inconclusive findings [54][55][56] . Thus, only the remaining eight reviews (seven systematic reviews and one meta-analysis) were included in our synthesis [57][58][59][60][61][62][63][64] . Figure 1 presents details of the search and inclusion and exclusion process.…”
Section: Resultsmentioning
confidence: 99%
“…One review of 6247 crc survivors who underwent surgery reported that the percentage of preoperatively potent men who experienced sexual dysfunction postoperatively ranged from 5% to 88% and that about half the women reported sexual dysfunction. The dysfunctions were more frequent and more pronounced in individuals treated for rectal cancer than in those treated for cancer of the colon and were worse if the patient had undergone rectal excision surgery or had received radiation treatments, or both 59 . Preoperative radiotherapy, a stoma, and complications during or after surgery were significantly associated with higher sexual dysfunction 59,64 .…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
See 3 more Smart Citations